2007
DOI: 10.1089/sur.2006.051
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Tobramycin in The Treatment of Ventilator-Associated Pneumonia: A Pilot Study

Abstract: Aerosolized tobramycin for the treatment of VAP appeared safe and effective in this pilot study. A larger study is warranted to determine if aerosolized tobramycin will lead to better outcomes than intravenous tobramycin when used for the treatment of VAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 24 publications
(17 reference statements)
2
64
0
4
Order By: Relevance
“…Several studies, most of them with small samples, have shown good outcomes in patients with VAP due to MDRAcinetobacter spp. treated with colistin [9], high-dose ampicillin-sulbactam [10], tetracyclines [11](doxycycline or minocycline) or aerosolized tobramycin [12]. However, the recorded clinical experience with these antibiotics is still limited and the reported studies of their use in the treatment of VAP are not randomized controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, most of them with small samples, have shown good outcomes in patients with VAP due to MDRAcinetobacter spp. treated with colistin [9], high-dose ampicillin-sulbactam [10], tetracyclines [11](doxycycline or minocycline) or aerosolized tobramycin [12]. However, the recorded clinical experience with these antibiotics is still limited and the reported studies of their use in the treatment of VAP are not randomized controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Ингаляционные ан тибиотики не используются в качестве монотерапии без системных препаратов, т. к. степень их адсорб ции в кровь низка (2-4 %) и недостаточна для лече ния сопутствующих НП инфекций. Частота побоч ных эффектов (нефро и нейротоксичность) при применении ингаляционных антибиотиков невысо ка [7,[12][13][14][15][16][17][18].…”
Section: заметки из практикиunclassified
“…and inhaled tobramycin (291). Patients with clinical symptoms of VAP or a new pulmonary infiltrate on a chest radiograph after 96 h of intubation were eligible for the study.…”
Section: Nosocomial Pneumoniamentioning
confidence: 99%